E-learning Courseware Development for Power Electronics Course - Krismadinata; Mulya, Rudi; Juwita, Monica Danni (International Journal of Interactive Mobile Technologies (iJIM), 2022)
Based on the results of studies in the power electronics course, it shows that learning outcomes in the power components of semiconductors and inverter systems are not satisfactory. Innovation in teaching materials is an alternative to increasing this competency. This paper purposes a learning module through e-learning that is valid, practical, and effective, therefore it can improve student learning outcomes and motivation. This study uses a research and development method with the Plomp development model. The research subjects were electrical engineering education students taking power electronics courses. The data analysis technique used is descriptive analysis technique to describe the validity, practicality, and effectiveness of the learning module through e-learning. The result of the research is a learning module through e-learning that is valid, practical, and effective on the component material of semiconductor and inverter power systems that can improve student learning outcomes and learning motivation